Management of temporomandibular disorders on violinists - Arif Winursito; Felix Anthony W. Wong; Seto Pramudita; Ista Meidarlina; Lisda Damayanti (Indonesian Journal of Prosthodontic, 2026)
Temporomandibular Joint Disorders (TMD) is musculoskeletal group syndrome involving temporomandibular joint, masticatory muscles, and related tissues. Symptoms that often appear are pain in the joint area, limited mouth opening, and jaw that locks easily. TMD is generally experienced by many violinists. The tilt of the head to one side when playing violin for a long period cause muscle tension and pain in the face and neck region. This case report aims to describe the treatment of TMD on violinist using occlusal splint. A 26 year old female violinist came to prosthodontic clinic with the main complaint of pain in the jaw when opening the mouth too wide and frequent pain in the facial muscles. The patient has a bruxism habit and anxiety for a long time, and had unbearable pain when opening her mouth. Dental impressions are preformed and an immediate splint was made at the first visit, then at the second visit the immediate splint was replaced with a stabilization splint which was used for 3 months and is given physical self-regulation instructions until the pain finally disappears. Occlusal splint therapy accompanied with physical self regulation can overcame TMD in violinist patient.